Cloud Solutions for Private Permissionless Blockchain Deployment - Grodzicka, Hanna; Kedziora, Michal; Madeyski, Lech (Computing and Informatics, 2021)
This paper aims to survey the security and scalability problems occurring in private permissionless blockchain systems and solutions to them. The emphasis is put on the blockchain systems hosted by cloud vendors in the form of Blockchain-as-a-Service (BaaS). The currently available solutions offered by the most appreciated cloud providers are reviewed. The most promising services are tested for the real deployment of the consent management system (CMS). Implementing the CMS atop BaaS leads to creating Consent-as-a-Service (CaaS). Through experiments, the proposed system's replication ability and its scalability are examined, along with assessing the feasibility of the consent management system development in the provided cloud environment.